2021
DOI: 10.1155/2021/6621921
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of miR‐18a‐5p and Galanin in Rat Lung Ischemia Reperfusion‐Mediated Response

Abstract: Lung ischemia reperfusion (IR) is known to occur after lung transplantation or cardiac bypass. IR leads to tissue inflammation and damage and is also associated with increased morbidity and mortality. Various receptors are known to partake in activation of the innate immune system, but the downstream mechanism of tissue damage and inflammation is yet unknown. MicroRNAs (miRNAs) are in the forefront in regulating ischemia reperfusion injury and are involved in inflammatory response. Here, we have identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…miR-18a-5p and miR-106a-5p, which have not been described in existing studies on AS, are jointly associated with acute heart failure [ 94 ]. miR-18a-5p plays a crucial role in apoptosis and ROS production mediated by ischemia-reperfusion injury [ 95 ]. Together with lncRNA GAS5 and FENDRR, miR-18a-5p also participates in the regulation of mitochondrial ROS generation and energy metabolism [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-18a-5p and miR-106a-5p, which have not been described in existing studies on AS, are jointly associated with acute heart failure [ 94 ]. miR-18a-5p plays a crucial role in apoptosis and ROS production mediated by ischemia-reperfusion injury [ 95 ]. Together with lncRNA GAS5 and FENDRR, miR-18a-5p also participates in the regulation of mitochondrial ROS generation and energy metabolism [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play important roles in the development of IRI (Kura et al, 2020). In lung IRI, miR-18a-5p regulates cellular ROS levels and affects the nuclear localization of NFE2L2 into the nucleus (Xiao et al, 2021). Ding et al demonstrated that the inhibition of miR-29a can ameliorate myocardial IRI by reducing oxidative stress and NLRP3-mediated pyroptosis (Ding et al, 2020).…”
Section: Validation Of Biomarkers By Wb and Qrt-pcr In A Rat Lung Tra...mentioning
confidence: 99%
“…Cai et al carried out a study on the expression of microRNAs in pulmonary ischemia in laboratory animals that had undergone pulmonary transplantation, discovering increased microRNA-206 levels [ 169 ]. Another experimental study reported decreased levels of microRNA-18a-5p in ischemic pulmonary tissue [ 170 ]. Qin et al studied the expression of microRNAs in multiorgan ischemia caused by hemorrhagic shock and identified an increased expression of microRNA-24a in the animal group in which hemorrhagic shock had been induced ( p < 0.05).…”
Section: Implications Of Genetic and Epigenetic Expression On Inflamm...mentioning
confidence: 99%